PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI CUACA DI KELAS III SD NEGERI 105375 SUKASARI - Dhea Wafiq Mawaddah; Muhammad Noer Fadlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Pop-Up Book Digital learning media on weather material in grade III of SD Negeri 105375 Sukasari to increase students' interest in learning. The type of research used is Research and Development (R&D) with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 20 grade III elementary school students and one class teacher. Data were obtained through validation questionnaires from material experts, media experts, teacher and student response questionnaires, and student learning interest questionnaires before and after using the media. The validation results show that the Pop-Up Book Digital media is included in the "Very Feasible" category with an average validity score of 67.05%. From the practical aspect, the results of the teacher and student questionnaires obtained an average score of 4.67 (Very Good), indicating that the media is easy to use and interesting. From the effectiveness aspect, the results of the N-Gain analysis showed an increase in learning interest by 36% with the "Moderate" category. This media has been proven to increase student engagement, attention, and motivation through three-dimensional visualizations, animations, and engaging narratives. Therefore, digital pop-up books are suitable as an alternative interactive and innovative learning medium for abstract topics such as weather, while also supporting the implementation of technology-based active learning in elementary schools.